Interest Limitation Rules and Corporate Tax Avoidance: A Cross-Country Analysis - Dewantara, Andreas Rossi (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2025)
This study examines the impact of interest limitation rules on corporate tax avoidance and financing decisions. Interest from debts is tax-deductible, making debt financing attractive for firms, yet it also poses a risk for tax avoidance, leading to global tax revenue losses estimated between $125 to $280 billion annually. Tax authorities have implemented rules limiting interest deductibility, such as the debt-to-equity ratio ("thin-capitalization rule") and the interest-to-EBITDA ratio ("earnings stripping rule"), to curb this. Using a novel regression discontinuity design and panel data from 33 countries, the study finds no strong evidence that these rules significantly deter tax avoidance. However, it suggests the thin-capitalization rule might be marginally more effective than the earnings stripping rule. Our study proposes that adjusting the debt-to-equity ratio threshold to 2:1 could yield better outcomes in reducing tax avoidance for countries with a thin-capitalization rule. For countries with an earnings stripping rule, a stronger enforcement is recommended. The study encourages future research to explore the interaction with other tax regulations, such as the de minimis rule and arm’s length principles.